Transformative Legal History and the (Re)Classification of the South African Law of Delict - Emile Zitzke (Potchefstroom Electronic Law Journal, 2023)
The South African law of delict is traditionally classified as a private-law discipline. This classification is usually made with reference to the actor, power and interest theories. According to the actor theory, private law regulates disputes between non-state actors inter se while public law regulates disputes involving the state. The power theory maintains that private law regulates disputes between equals while public law brings equality where inequality exists. The interest theory dictates that there are some interests that are individualistic (where private law steps in) while other interests belong to the public at large (the playing field of public law). In this article honouring Prof Willemien du Plessis's contribution to legal history it is argued that none of the above traditional theories of classification can be used effectively to classify the South African law of delict as a purely private-law discipline. Instead, our law of delict fulfils a hybrid role, straddling public and private law, with much transformative potential. Actor theorists fail to account for the fact that the South African law of delict today regulates disputes between non-state actors inter see as well as the law on state liability. The power theory crumbles in the South African law of delict's private-law classification because oftentimes one of the strong reasons invoked to impose liability on a wrongdoer is that wrongdoer's position of relative power over the victim. The interest theory sheds doubtful light on the classification of the South African law of delict because it is difficult to justify how individual-rights infringements are either purely private or public. In the end, relaxing the absoluteness of the claim that the South African law of delict exclusively falls in the domain of private law could assist us in recognising the role that delict could play in transforming South African society in line with constitutional aspirations, fostering the responsible use of power, and working towards the collective wellbeing of our society.